A preliminary assessment of Lu2Y2Al2O9:Pr (LuYAM:Pr) as a potential scintillator. (October 2016) - Drozdowski, Winicjusz; Witkowski, Marcin E.; Brylew, Kamil; Łachmański, Wiktor; Makowski, Michał; Wojtowicz, Andrzej J.; Turczyński, Sebastian; Pawlak, Dorota A.; Malinowski, Michał
Abstract: Lu2 Y2 Al2 O9 :Pr crystals have been grown by the micro-pulling-down method and their basic luminescence properties have been examined in order to estimate their utility for scintillator applications. The performed studies comprise the measurements of radioluminescence spectra as a function of temperature, photoluminescence emission and excitation spectra, and low temperature thermoluminescence glow curves. A comparison of the present results with those obtained recently for Y4 Al2 O9 :Pr indicates that in spite of a higher density Lu2 Y2 Al2 O9 :Pr is a much less promising material, which is mainly due to the absence of the fast Pr 3+ d-f emission. Highlights: LuYAM:Pr crystals have been grown by the μPD method. Radio-, photo-, and thermoluminescence of LuYAM:Pr have been studied. At RT fast d-f luminescence of Pr 3+ ions has not been detected.